Germination response of Salsola schweinfurthii (Chenopodiaceae) to salinity and winged perianth removal - Bhatt, A. (2016)
Salsola schweinfurthii is a perennial branched halophytic shrub that inhabits arid environments in and around the Arabian Peninsula. Its tolerance to extreme drought renders it suitable for urban arid landscaping. Germinability of intact and de-winged seeds (winged perianth removed) was determined under two photoperiods (0 and 12 hours light per day), three thermoperiods (daily low/high of 15/25, 20/30 and 25/35°C) and five salinity levels (0, 100, 200, 400 and 600 mM NaCl). Germination was maximised (93%) by de-winging and incubation in 12 hours light at 25/35°C. Intact and de-winged seeds both exhibited positive photoblastism. Germination of intact seeds was entirely prevented by the lowest level of salinity, and only slightly less prevented in de-winged seeds. Ability to germinate returned after saline solution was replaced with distilled water. The ability for S. schweinfurthii seeds to remain viable through a temporary period of salinity indicates an adaptation to unpredictable soil surface conditions in arid environments. Artificial propagation rates might be increased by removing perianths and sowing before or after mid-winter.